Pickering Emulsions: Recent Studies of Pickering Emulsions: Particles Make the Difference (Small 34/2016). Issue 34 (September 2016) - Wu, Jie; Ma, Guang‐Hui
Abstract : Pickering emulsions, stabilized by various micro‐ or nanoparticles with different structures, morphologies or other characteristics, possess distinctive properties and versatile functions comparing with classical emulsions stabilized by surfactants. In recent years their applications, especially in the biomedical field, have been carried out extensively and widely such as templates to prepare colloidosomes, as oral or topical delivery system. These emulsions are reviewed by J. Wu and G.‐H. Ma on page 4633.